2016
DOI: 10.1111/1755-5922.12231
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin in acute heart failure: Most recent update on clinical and preclinical evidence

Abstract: SummaryHeart failure continues to be a widely prevalent disease across the world, affecting millions of Americans annually. Acute heart failure (AHF) has a substantial effect on rising healthcare costs and is one of the major causes of morbidity and mortality. The search for new drugs for symptom relief and to improve long-term outcomes in heart failure has led to development of serelaxin, a recombinant human relaxin-2 hormone.Relaxin was discovered in pregnancy, but eventually found to have a number of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Of the three known relaxin genes, Relaxin-2 is the only relaxin known to circulate in the blood. Indeed, the circulating and/or cardiac levels of relaxin-2 have been reported to be increased in patients with congestive heart failure, suggesting the pathological significance of relaxin peptide in development and progression of heart disease (13) (14) (15).…”
mentioning
confidence: 99%
“…Of the three known relaxin genes, Relaxin-2 is the only relaxin known to circulate in the blood. Indeed, the circulating and/or cardiac levels of relaxin-2 have been reported to be increased in patients with congestive heart failure, suggesting the pathological significance of relaxin peptide in development and progression of heart disease (13) (14) (15).…”
mentioning
confidence: 99%
“…Moreover, relaxin has a good safely record based on human clinical trials for other indications (Said and Mukherjee ; Ghosh et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Ghosh et al. ). Several investigators reported that relaxin promotes angiogenesis in cycling and pregnant endometrium, skin wounds, muscle injury, and ischemic myocardium (reviewed in (Jeyabalan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Intravenous serelaxin (a relaxin-2 analog) has recently been shown to improve clinical symptoms and organ function when given at the time of hospital admission to patients with AHF. 14 In the present study, plasma concentrations of relaxin-2 (measured in 2 independent laboratories) were very low in patients admitted with AHF, regardless of whether they were non-pregnant AHF or PPCM patients.…”
Section: Study Limitationsmentioning
confidence: 99%